Therapeutic targeting of obesity-induced neuroinflammation and neurodegeneration - Zeng, Jialiu; Cheong, Lenny Yi Tong; Lo, Chih Hung (Frontiers in Endocrinology, 2025)
Obesity is a major modifiable risk factor leading to neuroinflammation and neurodegeneration. Excessive fat storage in obesity promotes the progressive infiltration of immune cells into adipose tissue, resulting in the release of pro-inflammatory factors such as cytokines and adipokines. These inflammatory mediators circulate through the bloodstream, propagating inflammation both in the periphery and in the central nervous system. Gut dysbiosis, which results in a leaky intestinal barrier, exacerbates inflammation and plays a significant role in linking obesity to the pathogenesis of neuroinflammation and neurodegeneration through the gut-brain/gut-brain-liver axis. Inflammatory states within the brain can lead to insulin resistance, mitochondrial dysfunction, autolysosomal dysfunction, and increased oxidative stress. These disruptions impair normal neuronal function and subsequently lead to cognitive decline and motor deficits, similar to the pathologies observed in major neurodegenerative diseases, including Alzheimer’s disease, multiple sclerosis, and Parkinson’s disease. Understanding the underlying disease mechanisms is crucial for developing therapeutic strategies to address defects in these inflammatory and metabolic pathways. In this review, we summarize and provide insights into different therapeutic strategies, including methods to alter gut dysbiosis, lifestyle changes, dietary supplementation, as well as pharmacological agents derived from natural sources, that target obesity-induced neuroinflammation and neurodegeneration.